Evidence-based airway management protocol for a critical ill patient in medical intensive care unit: Systematic review. (August 2022) - Admass, Biruk Adie; Endalew, Nigussie Simeneh; Tawye, Hailu Yimer; Melesse, Debas Yaregal; Workie, Misganaw Mengie; Filatie, Tesera Dereje
Abstract: Background: Airway management outside the theatre is performed either to resuscitate a physiologically unstable critically ill patients or to secure an emergency airway in the absence of essential equipments. It is a life saving procedure for critically ill and injured patients. Delaying in securing airway or awaking the patient is not an option in case of difficult airway in intensive care unit. Therefore, developing and implementation of an evidence-based airway management protocol is important. Objective: This review was conducted to develop a clear airway management protocol for a critical ill patient in medical intensive care unit. Methods: After formulating the key questions, scope, and eligibility criteria for the evidences to be included, a comprehensive search strategy of electronic sources was conducted. The literatures were searched using advanced searching methods from data bases and websites to get evidences on airway management of a critical ill patient. Duplication of literatures was avoided by endnote. Screening of literatures was conducted based on the level of significance with proper appraisal. This review was carried out in accordance with the preferred reporting items for systematic reviews and meta-analyses (PRISMA) 2020 statement. Results: A total of 626 articles were identified from data bases and websites using an electronic search. Of these articles, 95 were removed for duplication and 305 studies were excluded after reviewing their titles and abstracts. At the screening stage, 79 articles were retrieved and evaluated for the eligibility. Finally, 40 studies related to airway management of a critical ill patient in medical ICU were included in this systematic review. Conclusion: A critical ill patient needs oxygenation and ventilation support. A focused and rapid assessment, with special attention of the airway and hemodynamic status of the critical ill patient is paramount. An appropriate airway management option should be employed to resuscitate or to control an emergency airway of a critical ill patent. This could be non invasive ventilation or invasive airway intervention. Highlights: Airway management outside operating theatre is a common practice. A critical ill patient needs oxygenation and ventilation support. A focused airway assessment even in the most urgent situation is mandatory. Usage of appropriate airway management intervention is paramount.